Descriptions of memory rehabilitation group interventions for neurological conditions: a systematic review - Martin, Kristy-Jane; Sinclair, Emma; das Nair, Roshan (SAGE, 2016)
Objective: To establish what aspects of group-based cognitive rehabilitation for memory problems are reported, and to develop a checklist for authors, which may to improve reporting of these interventions in future studies. Data sources: A systematic search was conducted on Web of Knowledge, CINAHL, MEDLINE, AMED, EMBASE and PsycINFO electronic databases (last search: 01/05/2015). Review methods: Articles were included if the sample were adults with a neurological disorder, the intervention was group-based cognitive rehabilitation for memory problems, and if the study was a randomised controlled trial. Articles were independently screened for inclusion and data extracted by two researchers, with the third researcher arbitrating any disputes. Results: Fourteen studies were included in this review. The reporting of certain aspects of an intervention was found to be poor, particularly in relation to: duration of the programme (6 of 14 studies did not report), the development of the intervention (7 of 14 studies did not discuss), and the content and structure of intervention (7 of the 14 studies did not provide details). Conclusion: This review found that the overall reporting of memory rehabilitation content and format is poor. Refinement and adaption of pre-existing checklists to capture aspects of cognitive rehabilitation programmes may help authors when reporting complex interventions. A draft checklist is provided that could be refined and validated in further research.